Synthesis method and application of difunctional material for carbon dioxide capture and in-situ conversion

By synthesising dual-functional materials with calcium-containing solid waste and waste circuit boards, the problem of high cost of ICCU technology is solved, low-cost carbon dioxide capture and in-situ conversion is achieved, adsorption capacity and conversion rate are improved, and waste is provided. Resource utilization plan.

CN119114083AActive Publication Date: 2024-12-13TSINGHUA UNIVERSITY +1

Patent Information

Application Number
CN202411186509.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-27
Publication Date
2024-12-13
Estimated Expiration
2044-08-27

AI Technical Summary

Technical Problem

ICCU technology is costly and difficult to effectively utilize waste, resulting in low efficiency in carbon dioxide capture and in-situ conversion.

Method used

The method of extracting copper metals through organic acids and modifying calcium-based functional materials in situ is used to synthesize low-cost dual-functional materials for carbon dioxide capture and in situ conversion. The method includes waste PCB board treatment, calcium-containing solid waste pretreatment, precursor preparation and calcining steps to form a dual-functional material of calcium oxide, copper-magnesium composite oxide and copper oxide.

Benefits of technology

It realizes low-cost dual-functional material synthesis, improves the adsorption capacity of carbon dioxide and the conversion rate of carbon monoxide, reduces the cost of carbon emission reduction, and provides a new idea of ​​resource utilization of waste.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119114083A_ABST
    Figure CN119114083A_ABST
Patent Text Reader

Abstract

The invention relates to a synthesis method and application of a difunctional material for carbon dioxide capture and in-situ conversion. According to the method, the calcium-containing solid waste and the waste circuit board are used as raw materials, copper metal is extracted by adopting organic acid, and the sintering problem of the calcium-based material is relieved in a mode of modifying the calcium-based functional material in situ, so that the ICCU bifunctional material can be synthesized at low cost. Therefore, the synthesis method provided by the invention not only provides a new thought for resource utilization of the calcium-containing solid waste and the PCB and improvement of carbon emission reduction benefits, but also reduces the cost of the existing ICCU bifunctional material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of carbon dioxide capture and conversion and utilization, and provides a method for synthesizing a dual-functional material for carbon dioxide capture and in-situ conversion using waste, and uses of the dual-functional material. Background Art

[0002] Carbon capture, utilization and storage (CCUS) has always been a hot topic of concern in the international community and is considered to be one of the most promising and effective means of emission reduction.

[0003] In the carbon capture stage of CCUS technology, calcium-based absorbent cyclic CO2 capture technology has become a research hotspot due to its advantages such as easy availability of raw materials, large theoretical capture capacity, and fast capture rate. The absorbent developed based on the traditional calcium cycle has become a research hotspot. At present, the main factor affecting the large-scale application of calcium-based absorbent cyclic CO2 capture technology is that as the cycle reaction proceeds, the CO2 capture performance of the calcium-based absorbent tends to decay due to high-temperature sintering. At present, the main modification methods include heating pretreatment and hydration reaction pretreatment, adding inert supports, and using organic acids to acidify natural calcium-containing minerals.

[0004] Patent document 1 (CN117463343A) discloses a method for synthesizing a carbon dioxide adsorption-catalysis dual-function material, which comprises leaching high-calcium solid waste with a solution containing an organic acid to obtain a mixture, filtering the mixture and mixing the obtained filtrate with a soluble active metal salt, a soluble metal auxiliary salt and an acidic complexing agent to obtain a mixed solution, and subjecting the mixed solution to gelling treatment, calcination and reduction, thereby obtaining a carbon dioxide adsorption-catalysis dual-function material. The high-calcium solid waste is selected from at least one of steel slag, carbide slag, ore powder slag and desulfurization slag, and the soluble active metal salt is selected from at least one of the nitrates of Ru, Rh, Pt, Ni and Co. As can be seen from the above, the active metal components in Patent Document 1 are not extracted from waste and cannot be said to be economical.

[0005] In addition, in recent years, a disruptive technology has emerged in the CCUS field, namely, carbon dioxide capture and in-situ conversion technology (ICCU). The key to this technology is to use a dual-functional material that can simultaneously capture carbon dioxide and convert it in situ to achieve in-situ capture and utilization, which can save the cost of CO2 compression and transportation and reduce the risk of CO2 leakage. At the same time, ICCU technology can reduce the regeneration temperature of calcium-based adsorbents and alleviate the problem of material sintering. Although ICCU technology has greatly reduced costs compared to traditional CCUS technology, it still faces the problem of high costs. Summary of the invention

[0006] Problem that the invention aims to solve

[0007] In view of the high cost of ICCU technology, a method for synthesizing dual-functional materials at low cost by fully utilizing waste is needed. At the same time, a technology for capturing carbon dioxide and synthesizing carbon monoxide, an important component of syngas in industry, in situ by using ICCU technology is also needed.

[0008] Solutions for solving problems

[0009] Calcium-containing solid waste (referred to as "calcium-containing solid waste") such as eggshells, shells, carbide slag, snail shells, red mud, etc. are important components of solid waste. Calcium-containing solid waste such as eggshells has a high proportion of organic matter and calcium, which can easily cause environmental pollution and breed bacteria. At present, the recovery rate of calcium-containing solid waste is low, and most of the calcium-containing solid waste is directly discarded, and a large-scale and industrialized treatment system has not yet been formed. Calcium-containing solid waste such as eggshells is mainly composed of calcium carbonate (CaCO3), accounting for about 94% of the eggshell mass, which is an ideal calcium recycling raw material. In addition, with the accelerated replacement of electronic products, the amount of printed circuit board (PCB) waste has increased year by year, and its resource utilization also has problems. The current waste treatment methods are mainly landfill and incineration, which can easily lead to soil pollution and air pollution. PCB boards contain a large amount of copper, and the copper content accounts for more than 90% of the metal content, which is an ideal reverse water gas shift catalytic material. In the resource utilization of carbon dioxide, reverse water gas shift can obtain carbon monoxide, the main component of industrial synthesis gas, which has wide utilization value. Its main non-precious metal catalysts include copper, nickel, iron, etc. Therefore, the present invention proposes a dual-functional material synthesis process based on calcium-containing solid waste and waste circuit boards.

[0010] In addition, in the organic acid treatment of waste, a large amount of gas released during the calcination of the acidified organic acid salt can improve the microscopic pore structure of the adsorbent, thereby improving the adsorption performance of CO2. Therefore, the present invention proposes a method for combining the waste recovery and adsorption material modification process by organic acid.

[0011] Based on the above, the present invention provides a synthesis method using calcium-containing solid waste and waste circuit boards as raw materials, extracting copper metal with organic acid, and alleviating the sintering problem of calcium-based materials by in-situ modification of calcium-based functional materials, thereby synthesizing ICCU dual-functional materials at low cost. Therefore, the synthesis method of the present invention not only provides a new idea for the resource utilization of calcium-containing solid waste and PCB boards, but also reduces the cost of existing ICCU dual-functional materials.

[0012] Specifically, the present invention provides a method for synthesizing a dual-functional material for carbon dioxide capture and in-situ conversion, which comprises the following steps:

[0013] Waste PCB board processing step S1: After calcining the waste PCB board, crush it into powder, add it into an aqueous solution of organic acid and stir it, then remove the residue to obtain a copper-containing organic acid solution;

[0014] Calcium-containing solid waste pretreatment step S2: calcining the calcium-containing solid waste powder to obtain a calcium oxide-containing product;

[0015] Precursor preparation step S3: mixing the calcium oxide-containing product in step S2 with the copper-containing organic acid solution in step S1 and heating to evaporate to dryness, thereby obtaining a precursor containing copper and calcium;

[0016] Calcination step S4: calcining and reducing the precursor obtained in step S3 to obtain the dual-functional material.

[0017] According to the above-mentioned synthesis method, the calcium-containing solid waste includes one or more of waste eggshells, shells, carbide slag, snail shells, fly ash, and red mud;

[0018] The organic acid is selected from one or more of oxalic acid, formic acid, acetic acid, propionic acid and tartaric acid; the concentration of the aqueous solution of the organic acid is 0.01-1 mol / L, and the pH value is 1-3.

[0019] According to the synthesis method described above, in step S1, the ratio of the powder of the waste PCB board to the aqueous solution of the organic acid is (0.01g-0.05g):1ml.

[0020] According to the above-described synthesis method, in step S1, the calcination temperature is 800-1000° C., and the calcination time is 1-3 hours.

[0021] According to the above-described synthesis method, in step S2, the calcium-containing solid waste powder is calcined at a temperature of 800 to 1000° C. and a calcination time of 1 to 3 hours.

[0022] According to the above-described synthesis method, in step S3, the ratio of the calcium oxide-containing product to the copper-containing organic acid solution is (0.01 g to 0.05 g):1 ml; and the heating temperature is 80 to 100°C.

[0023] According to the above-described synthesis method, in step S4, the precursor is calcined at a temperature of 700 to 900° C. and a calcination time of 1 to 3 hours.

[0024] The present invention also provides a dual-functional material obtained by the above-mentioned synthesis method, wherein the dual-functional material comprises calcium oxide, copper-magnesium composite oxide and copper oxide.

[0025] According to the above dual-functional material, the copper loading in the dual-functional material is 0.2wt%-0.5wt%.

[0026] The present invention further provides a bifunctional material obtained by the above-mentioned synthesis method or use of the above bifunctional material in carbon dioxide capture and in-situ conversion reaction to generate carbon monoxide.

[0027] Effects of the Invention

[0028] The above technical solution of the present invention has the following beneficial effects:

[0029] 1) The synthesis method of the present invention is a low-cost dual-functional material synthesis process: this process utilizes two major wastes - copper extracted from waste circuit boards and calcium oxide recovered from calcium-containing solid waste to form a material with adsorption and catalytic functions, which can fully utilize waste resources, reduce costs, and improve carbon emission reduction benefits.

[0030] 2) The present invention performs performance optimization: by adjusting synthesis parameters such as the type of organic acid, the content of copper loading, and the content of modified acid, the structure and composition of the bifunctional material are optimized to have a higher adsorption capacity, better stability, and a higher carbon monoxide conversion rate.

[0031] 3) The present invention provides a new application mode for two major solid wastes: the ICCU dual-function material synthesis process of the present invention can be combined with the existing waste PCB treatment process. After the waste PCB boards are incinerated, copper, magnesium, calcium and other metals are leached out with organic acid for dual-function material synthesis, and the remaining insoluble precious metals can be further electrolytically refined.

[0032] 4) The method of the present invention can be produced on an industrial scale; currently, the utilization rate of calcium-containing solid waste resources is low, and the present invention explores the possibility of utilizing calcium-containing solid waste. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 The synthesis process of the dual-functional material of the present invention is shown.

[0034] Figure 2 The crystal structure of the acid-modified calcium-based bifunctional material is shown.

[0035] Figure 3 The cyclic carbon capture performance of the modified bifunctional materials is shown.

[0036] Figure 4 The carbon capture and in-situ conversion (ICCU) cycle carbon capture performance of the modified dual-functional material is shown.

[0037] Figure 5 The carbon capture and in-situ conversion (ICCU) cyclic carbon conversion performance of the modified dual-functional material is shown.

[0038] Figure 6The performance of modified bifunctional materials for carbon capture and in-situ conversion (ICCU) cycle production of CO is shown. DETAILED DESCRIPTION

[0039] The following describes the embodiments of the present invention, but the present invention is not limited thereto. The present invention is not limited to the various structures described below, and various changes can be made within the scope of the invention claim, and the embodiments and embodiments obtained by appropriately combining the technical means disclosed in different embodiments and embodiments are also included in the technical scope of the present invention. In addition, all the documents recorded in this specification are cited in this specification as references.

[0040] Unless defined otherwise, technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs.

[0041] In this specification, the numerical range expressed using "a numerical value A to a numerical value B" means a range including the endpoints A and B.

[0042] Unless otherwise required in this application, throughout the specification and the claims that follow, the word "comprising" should be interpreted in its open, inclusive sense, ie, "including, but not limited to."

[0043] In this specification, unless otherwise specified, the word "multiple" in "multiple", "multiple", "plurality", etc. means a numerical value of 2 or more.

[0044] In the present specification, the term “substantially”, “substantially” or “essentially” means that the error is less than 5%, less than 3% or less than 1% compared with the relevant perfect standard or theoretical standard.

[0045] In this specification, the word "may" includes both performing a certain process and not performing a certain process.

[0046] In the present specification, "optional" or "optionally" means that the event or situation described below may or may not occur, and the description includes cases where the event occurs and cases where it does not occur.

[0047] In this specification, if "room temperature", "normal temperature" or the like appears, the temperature may generally be 25°C±2°C.

[0048] The "calcium-based material" described in the present invention mainly refers to calcium oxide, and may also contain a small amount of calcium carbonate.

[0049] In view of the problem of high cost of current ICCU technology, the present invention provides a low-cost dual-functional material synthesis method using waste as raw materials, and also explores the feasibility of new waste recycling.

[0050] Specifically, the synthesis method of the present invention comprises the following steps:

[0051] Waste PCB board processing step S1: After calcining the waste PCB board, crush it into powder, add it into an aqueous solution of organic acid and stir it, then remove the residue to obtain a copper-containing organic acid solution;

[0052] Calcium-containing solid waste pretreatment step S2: calcining the calcium-containing solid waste powder to obtain a calcium oxide-containing product;

[0053] Precursor preparation step S3: mixing the calcium oxide-containing product in step S2 with the copper-containing organic acid solution in step S1 and heating to evaporate to dryness, thereby obtaining a precursor containing copper and calcium;

[0054] Calcination step S4: calcining and reducing the precursor obtained in step S3 to obtain the dual-functional material.

[0055] Figure 1 The synthesis process of the dual-functional material of the present invention is schematically shown in FIG. Figure 1 The copper metal is recovered by acid leaching from the solid waste (called PCB board solid waste pyrolysis residue) to obtain a copper-containing organic acid solution. On the other hand, the calcium-containing solid waste is calcined to obtain a calcium oxide-containing product. Then, the copper-containing organic acid solution is mixed with the calcium oxide-containing product to modify the calcium-based material and load the metal to obtain a precursor containing copper and calcium. The precursor is calcined to obtain a dual-functional material.

[0056] Each step is described in detail below.

[0057] Step S1

[0058] In the synthesis method of the present invention, the waste PCB board is first calcined and then crushed to obtain the powder of the waste PCB board (hereinafter referred to as "PCB powder"). The temperature of calcining the PCB board can be 800-1000°C and the calcination time can be 1-3 hours. If the calcination temperature is too low, the organic matter in the PCB board cannot be completely removed.

[0059] The present invention adopts an organic acid leaching method to extract copper from the calcined PCB board. Specifically, the calcined PCB powder is added to an organic acid aqueous solution, stirred and acid-leached, and after sufficient reaction, the residue is removed by suction filtration to obtain a copper-containing organic acid solution. The copper-containing organic acid solution will be used to modify the calcium-based material and synthesize the dual-functional material.

[0060] In the present invention, the organic acid can be selected from one or more of oxalic acid, formic acid, acetic acid, propionic acid, and tartaric acid. The concentration of the aqueous solution of the organic acid can be 0.01 to 1 mol / L, and the pH value can be 1 to 3. The reason is that too low acid concentration has a poor modification effect on the dual-functional material; too high acid concentration will increase the cost.

[0061] The ratio of waste PCB powder to organic acid aqueous solution can be (0.01g~0.05g):1ml. Therefore, 1-5g PCB powder can be added to every 100ml organic acid solution. After adding PCB powder, stir for a certain time, and then filter to remove insoluble impurities. The stirring time can be 2~5h.

[0062] In step S1, in order to adjust the copper ion concentration, an appropriate amount of an organic acid aqueous solution of the same concentration may be optionally added to the copper-containing organic acid solution after the residue is removed, so as to dilute the copper ions to a suitable concentration.

[0063] In actual industrial production, the waste PCB board treatment and acid leaching process can be combined with the heat treatment or incineration method in the existing PCB treatment technology, and a waste gas treatment device can be added. In addition, after extracting a large amount of elements such as copper, magnesium, and calcium by the acid leaching method of the present invention, the remaining precious metals can be further refined by electrolysis. The advantage of the PCB board treatment method of the present invention is that the acid leaching process is combined with the organic acid modification process of the dual-functional material, the steps are simple, the cost is reduced, and it can be combined with existing mature technologies.

[0064] Step S2

[0065] In the present invention, the calcium-containing solid waste described in step S2 may include one or more of discarded eggshells, shells, carbide slag, snail shells, fly ash, and red mud. When the calcium-containing solid waste is eggshells, shells, or snail shells, the main component is calcium carbonate; when the calcium-containing solid waste is carbide slag, fly ash, or red mud, the main component is calcium oxide.

[0066] When the calcium-containing solid waste is shells, carbide slag, snail shells or red mud, it can be directly calcined after being crushed into powder to obtain a calcium oxide-containing product.

[0067] When the calcium-containing solid waste is waste eggshells, in order to prevent the organic matter in the eggshell membrane from participating in the reaction, the powder of the waste eggshells needs to be separated from the eggshell membrane.

[0068] For example, the eggshells can be crushed and the powder can be soaked in water, the turbid liquid can be fully stirred and allowed to stand for 10 to 30 minutes, the film on the top of the liquid can be separated from the eggshells at the bottom, and then the eggshell powder can be dried and calcined in a muffle furnace to obtain a calcium oxide-containing product made from eggshells.

[0069] In step S2, the calcium-containing solid waste powder can be calcined at a temperature of 800-1000°C and a calcination time of 1-3 hours. The reason is that if the calcination temperature is too low or the calcination time is too short, the calcium carbonate cannot be completely decomposed; and if the calcination time is too long, the material is prone to sintering.

[0070] Step S3

[0071] In step S3, the calcium oxide product obtained in step S2 is mixed with the copper-containing organic acid solution in step S1, and heated in an oil bath with stirring until completely evaporated to obtain a copper-containing organic calcium precursor. In step S3, calcium oxide is modified using an organic acid.

[0072] The heating temperature in step S3 can be 80-100° C. The ratio of the calcium oxide-containing product to the acid solution for modification is (0.01 g-0.05 g):1 ml. The reason is that the material with a high amount of modified acid has better carbon capture performance, while too high a modified acid amount will increase the cost of the material.

[0073] Step S4

[0074] The copper-containing organic calcium precursor obtained in step S3 is calcined and reduced in a muffle furnace to obtain a dual-functional material.

[0075] In the present invention, the precursor is calcined at a temperature of 700-900°C for 1-3 hours. The reason is that if the calcination temperature is too low, the material cannot be completely decomposed; if the calcination temperature is too high, the material will sinter.

[0076] The reduction can be performed in a pure hydrogen atmosphere at 800 to 1000° C. The temperature during the reduction can be, for example, 850° C., 900° C., 950° C., etc.

[0077] The working principle of the present invention is based on the recycling of waste circuit boards and calcium-containing solid waste, realizing a low-cost preparation method of in-situ carbon dioxide capture and conversion (ICCU) dual-functional materials. The specific working principle is:

[0078] Extracting copper from waste circuit boards: After heat treatment, waste circuit boards are oxidized to copper oxide, which is then leached with organic acid to react with copper oxide to obtain copper-containing acid. The organic acid produced in this step not only recovers valuable metal resources, but also plays a role in modifying calcium oxide in subsequent steps.

[0079] Calcium-based materials for recycling calcium-containing solid waste: Calcium-based materials, as the main component of calcium recycling absorbents, have a high ability to adsorb CO2.

[0080] Modification to improve performance: Organic acid is not only used to extract copper from waste circuit boards, but also to modify calcium oxide. The modified calcium oxide has better stability, solves the problem of easy sintering of traditional calcium cycle capture technology, and improves the cycle life of the capture material.

[0081] From the above, it can be seen that the present invention utilizes copper extracted from waste circuit boards and calcium-based materials recovered from calcium-containing solid waste to form materials with adsorption and catalytic functions, which fully utilizes waste gas resources, reduces costs, and improves carbon emission reduction benefits.

[0082] Furthermore, the present invention also provides a bifunctional material obtained by the above-mentioned synthesis method, wherein the bifunctional material comprises calcium oxide, copper-magnesium composite oxide and copper oxide.

[0083] The copper loading in the dual-functional material of the present invention is 0.2wt%-0.5wt%. The reason is that, through experiments, it is found that the carbon capture amount of the material with a copper content of 0.2wt% is still stable at about 9mmol / g after ten ICCU cycles, and the carbon capture amount of the material with a copper content of 0.5wt% is still stable at about 6mmol / g after ten ICCU cycles. At the same time, the conversion rate of the two reactions is about 80%, which has excellent comprehensive performance. Too low copper concentration will lead to poor catalytic effect and low conversion rate; too high copper concentration will cause the material to have sintering problems, and its carbon capture amount is poor.

[0084] In addition, the present invention also provides a bifunctional material obtained by the above-mentioned synthesis method or use of the above-mentioned bifunctional material in carbon dioxide capture and in-situ conversion reaction to generate carbon monoxide.

[0085] Specifically, the above-mentioned dual-functional material of the present invention is granulated and screened, and a sample with a particle size of 0.35-0.45 mm is selected and placed in a fixed reaction bed at normal pressure, and the air in the reaction system is removed by nitrogen. The sample is reduced under pure hydrogen conditions, and then enters a cycle: each cycle alternately passes a mixture of carbon dioxide and nitrogen and pure hydrogen to simulate the carbon dioxide capture and in-situ conversion process. The results show that the dual-functional material of the present invention exhibits excellent carbon dioxide capture capacity, excellent conversion rate and selectivity in the ICCU cycle.

[0086] Example

[0087] The embodiments of the present invention will be described in detail below in conjunction with the examples, but those skilled in the art will appreciate that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If no specific conditions are specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.

[0088] Example 1

[0089] according to Figure 1 The technical principle of the present invention is shown to prepare the ICCU dual-functional material, which is specifically as follows:

[0090] (1) Take a conventional PCB board and calcine it at 900℃ in a muffle furnace for 2h, grind it into powder. Take 0.18g of oxalic acid solid and dissolve it in 100ml of deionized water. After it is completely dissolved, add 2g of PCB powder, stir it on a magnetic stirrer at 200 rpm for 4h, and filter it to obtain a copper-containing acid solution.

[0091] (2) conventional discarded egg shells were cleaned and ground into powder, rinsed with clean water and allowed to stand to remove the biofilm, and after the shell and membrane were separated, the egg shells with membrane removed at the bottom of the solution were dried and calcined in a muffle furnace at 900°C for 2h.

[0092] (3) Add 2.26 g of the calcined eggshells to 100 ml of the acid solution in step (1), heat in an oil bath at 90° C. and stir at 200 rpm until evaporated to dryness.

[0093] (4) The evaporated solid was calcined in a muffle furnace at 800°C for 2 h, and reduced at 900°C in a pure hydrogen atmosphere to obtain the ICCU dual-functional material.

[0094] Example 2-1

[0095] The catalyst synthesis process is basically the same as that in Example 1, except that the acid solution preparation method and the amount of eggshell added are changed. Step (1) in this example: 40 ml of pure acetic acid is added to 50 ml of deionized water to uniformly dissolve, 2 g of PCB powder is added, and the mixture is stirred on a magnetic stirrer at 200 rpm for 4 h, and filtered to obtain an original acid solution; 165 ml of acetic acid (50% by volume) of the same concentration is added to the original acid solution to dilute the mixture to obtain 265 ml of acid solution.

[0096] Step (3) in this example: add 6 g of calcined eggshells to the obtained 265 ml of acid solution, and keep the rest the same.

[0097] Example 2-2

[0098] The catalyst synthesis process is basically the same as that in Example 2, except that the mass of eggshell added in step (4) is changed to 12 g of calcined eggshell added to the obtained 265 ml of acid solution, and the rest remains the same.

[0099] Example 3-1

[0100] The catalyst synthesis process is basically the same as that in Example 1, except that the acid solution preparation method and the mass of eggshell added are changed. Step (1) in this example: 2 g of oxalic acid is added to 100 ml of deionized water to uniformly dissolve, and then 3 g of PCB powder is added. The mixture is stirred on a magnetic stirrer at 200 rpm for 12 h, and filtered to obtain an original acid solution. 50 ml of oxalic acid of the same concentration is added to the original acid solution to dilute the mixture to obtain 150 ml of acid solution.

[0101] Step (3) in this example: 2 g of calcined eggshells were added to the obtained 150 ml acid solution, and the rest remained the same. In this example, the Cu loading was 0.8 wt % relative to the mass of the obtained ICCU dual-functional material.

[0102] Example 3-2

[0103] The catalyst synthesis process is basically the same as that in Example 1, except that the acid solution preparation method and the amount of eggshell added are changed. Step (1) in this example: 2 g of oxalic acid is added to 100 ml of deionized water to uniformly dissolve, and then 3 g of PCB powder is added. The mixture is stirred on a magnetic stirrer at 200 rpm for 12 h, and filtered to obtain an original acid solution. 87.5 ml of oxalic acid of the same concentration is added to 62.5 ml of the original acid solution to dilute the mixture to obtain 150 ml of acid solution.

[0104] Step (3) in this example: 2 g of calcined eggshells were added to the obtained 150 ml acid solution, and the rest remained the same. In this example, the Cu loading was 0.5 wt % relative to the mass of the obtained ICCU dual-functional material.

[0105] Example 3-3

[0106] The catalyst synthesis process is basically the same as that in Example 1, except that the acid solution preparation method and the amount of eggshell added are changed. Step (1) in this example: 2 g of oxalic acid is added to 100 ml of deionized water to uniformly dissolve, and then 3 g of PCB powder is added. The mixture is stirred on a magnetic stirrer at 200 rpm for 12 h, and filtered to obtain an original acid solution. 125 ml of oxalic acid of the same concentration is added to 25 ml of the original acid solution to dilute the mixture to obtain 150 ml of acid solution.

[0107] Step (3) in this example: 2 g of calcined eggshells were added to the obtained 150 ml acid solution, and the rest remained the same. In this example, the Cu loading was 0.2 wt % relative to the mass of the obtained ICCU dual-functional material.

[0108] Example 4

[0109] The catalyst synthesis process is basically the same as that in Example 1, except that the acid solution preparation method and the mass of eggshell added are changed. Step (1) in this example: 5 g of oxalic acid is added to 200 ml of deionized water and uniformly dissolved, then 7 g of PCB powder is added, stirred at 200 rpm on a magnetic stirrer for 12 h, and filtered to obtain a modified acid solution.

[0110] XRD characterization of dual-functional materials

[0111] Example 4 was selected for XRD characterization, and the results are shown in Figure 2 It can be observed that the bifunctional material is mainly calcium oxide, copper-magnesium composite oxide and part of copper oxide.

[0112] Application Examples

[0113] Carbon capture performance test of dual-function materials

[0114] The three dual-functional materials prepared in Example 3 were selected and pure eggshell was used as a control to test the carbon capture capacity by thermogravimetry. The reaction conditions were carbonation at 650°C in a 15% CO2 atmosphere and calcination at 900°C in a 80% CO2 atmosphere for 25 cycles. The results are shown in Figure 2. Figure 3 shown.

[0115] Depend on Figure 3 As shown, the carbon capture capacity of the materials of Example 3-2 and Example 3-3 (0.5wt% copper content and 0.2wt% copper content) with lower Cu concentration is better, while the carbon capture capacity of Example 3-1 with higher copper content is poor in thermogravimetric analysis, which is similar to the carbon capture performance of the original eggshell. It is speculated that the reason is that the Tammann temperature of copper is low, and the high concentration causes sintering of the material; the carbon capture capacity of Example 3-2 and Example 3-3 with lower Cu concentration is not much different in thermogravimetric analysis.

[0116] Test of carbon capture capacity and catalytic performance of ICCU cycle of dual-functional materials

[0117] The three bifunctional materials prepared in Example 3 were selected to simulate the ICCU process on a fixed reactor bed at normal pressure, and the carbon capture capacity was tested, and the conversion rate and CO selectivity were calculated. In each cycle, a mixture of carbon dioxide and nitrogen (CO2: N2 = 1: 9) was first passed at 650°C, with a ventilation volume of 50 ml / min, for 0.5 h, and then pure hydrogen was passed at 650°C, with a ventilation volume of 50 ml / min, for 0.5 h. The results are shown in Figure 2. Figures 4 to 6 shown.

[0118] Depend on Figure 4 It can be seen that Example 3-3, i.e., the material with a Cu mass fraction of 0.2%, has the highest carbon capture capacity per cycle and exhibits the best carbon capture capacity in the ICCU cycle. Figure 5 and Figure 6It can be seen that the material with a Cu mass fraction of 0.2% also shows excellent conversion rate and selectivity in the ICCU cycle. After comprehensive consideration, the material with a Cu mass fraction of 0.2% was modified with oxalic acid and has excellent performance.

[0119] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and variations will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or technical improvements in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.

Claims

1. A method for synthesizing a dual-functional material for carbon dioxide capture and in-situ conversion, comprising the following steps: Waste PCB board processing step S1: After calcining the waste PCB board, crush it into powder, add it into an aqueous solution of organic acid and stir it, then remove the residue to obtain a copper-containing organic acid solution; Calcium-containing solid waste pretreatment step S2: calcining the calcium-containing solid waste powder to obtain a calcium oxide-containing product; Precursor preparation step S3: mixing the calcium oxide-containing product in step S2 with the copper-containing organic acid solution in step S1 and heating to evaporate to dryness, thereby obtaining a precursor containing copper and calcium; Calcination step S4: calcining and reducing the precursor obtained in step S3 to obtain the dual-functional material.

2. The synthesis method according to claim 1, wherein the calcium-containing solid waste comprises one or more of waste eggshells, shells, carbide slag, snail shells, fly ash, and red mud; The organic acid is selected from one or more of oxalic acid, formic acid, acetic acid, propionic acid and tartaric acid; the concentration of the aqueous solution of the organic acid is 0.01-1 mol / L, and the pH value is 1-3.

3. The synthesis method according to claim 1 or 2, wherein in step S1, the ratio of the powder of the waste PCB board to the aqueous solution of the organic acid is (0.01g-0.05g):1ml.

4. The synthesis method according to any one of claims 1 to 3, wherein in step S1, the calcination temperature is 800 to 1000°C and the calcination time is 1 to 3 hours.

5. The synthesis method according to any one of claims 1 to 4, wherein in step S2, the calcium-containing solid waste powder is calcined at a temperature of 800 to 1000°C and a calcination time of 1 to 3 hours.

6. The synthesis method according to any one of claims 1 to 5, wherein in step S3, the ratio of the calcium oxide-containing product to the copper-containing organic acid solution is (0.01 g to 0.05 g): 1 ml; and the heating temperature is 80 to 100°C.

7. The synthesis method according to any one of claims 1 to 6, wherein in step S4, the precursor is calcined at a temperature of 700 to 900°C and a calcination time of 1 to 3 hours.

8. A bifunctional material obtained by the synthesis method according to any one of claims 1 to 7, wherein the bifunctional material comprises calcium oxide, copper-magnesium composite oxide and copper oxide.

9. The dual-functional material according to claim 8, wherein the copper loading in the dual-functional material is 0.2 wt%-0.5 wt%.

10. Use of a bifunctional material obtained by the synthesis method according to any one of claims 1 to 7 or a bifunctional material according to claim 8 or 9 in carbon dioxide capture and in-situ conversion reaction to generate carbon monoxide.

Citation Information

Patent Citations

  • Composite adsorbent for biogas desulfurization and decarburization as well as preparation method and application of the composite adsorbent

    CN111569821A

  • Heterogeneous nano-copper catalyst as well as preparation method and application thereof

    CN113262786A

  • Calcium oxide loaded nano copper oxide catalyst as well as preparation method and application thereof

    CN115254125A

  • Carbon dioxide adsorption-catalysis bifunctional material as well as preparation method and application thereof

    CN117463343A

  • Method for recycling cathode copper by using circuit board organic acid super-coarsening waste liquid

    CN117661037A

Cited By

  • Cu-Al-Ca bifunctional material with core-shell structure as well as preparation method and application of Cu-Al-Ca bifunctional material

    CN119701864A